Cardiac Complications of COVID-19 Infection and the Role of Physical Activity. Issue 1 (15th January 2023) - Smer, Aiman; Squires, Ray W.; Bonikowske, Amanda R.; Allison, Thomas G.; Mainville, Rylie N.; Williams, Mark A.
Abstract : Although coronavirus disease-2019 (COVID-19) primarily affects the lungs, cardiovascular complications are not uncommon. Higher fitness prior to infection is associated with less severe disease. Peak VO2 in patients with post-COVID-19 syndrome is substantially below predicted values in many patients. A gradual return to exercise after COVID-19 is advised. Abstract : Since December 2019, the newly emerging coronavirus has become a global pandemic with >250 million people infected and >5 million deaths worldwide. Infection with coronavirus disease-2019 (COVID-19) causes a severe immune response and hypercoagulable state leading to tissue injury, organ damage, and thrombotic events. It is well known that COVID-19 infection predominately affects the lungs; however, the cardiovascular complications of the disease have been a major cause of morbidity and mortality. In addition, patients with cardiovascular disease are vulnerable to contract a severe form of the illness and increased mortality. A significant number of patients who survived the disease may experience post-COVID-19 syndrome with a variety of symptoms and physical limitations. Here, we review the cardiac complications of COVID-19 infection and the results of cardiopulmonary exercise testing and guidelines for exercise training after infection.